A generous review of fly ash engineering characteristics on concrete in trait of compressive strength. (26th October 2022) - Shaw, Sayan Kumar; Sil, Arjun
Fly ash is a fine grey powder consisting mostly of spherical, glassy particles produced as a by-product in coal-fired power stations having pozzolanic properties that exhibits supplementary cementitious material. This paper essentially investigated about the effects of fly ash on concrete 'with and without admixture, and as well as mixed form' in aspect of water-binder ratio, fly ash replacement percentages and curing ages (days). For modelling and analysis of these properties statistical best fit functions were used. This comprehensive study shows that in all types of concrete, compressive strength decreasing with increasing water-binder ratio. However, in maximum cases, highest compressive strength observed in case of 'with admixture fly ash concrete' is at 20% fly ash (FA) replacement level and shows maximum strength gaining initiates between 7-90 days in case of 'with admixture FA concrete' whereas significant strength gaining observed after 90 days onwards and ultimate strength gaining at 365 days.